Pemanfaatan Koleksi Repository Bagi Mahasiswa Di Perpustakaan Sekolah Tinggi Ilmu Pertanian Agrobisnis Perkebunan - Sunyianto Sunyianto; Friska Anggraini Barus (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2023)
At the Medan Plantation Agribusiness Agricultural College (STIP-AP), the library also has a collection of repositories that are diverse and useful for students. This repository provides easy and fast access to scientific literature and academic works relevant to the fields of agriculture, agribusiness and plantation science. The purpose of this rich writing is to examine the use of repository collections by students at the Medan STIP-AP library and the factors that influence it. This study uses qualitative research methods to understand the use of repository collections by students at the STIP-AP Medan Library. This method involves selecting informants, collecting data through in-depth interviews and participatory observation, analyzing qualitative data, and paying attention to the validity and reliability of the data. This research also maintains research ethics by securing the confidentiality of information and participant privacy. The aim is to provide an in-depth understanding of the utilization of repository collections and provide input for the development of library services. The result of this work is that the utilization of the repository collection in the STIP-AP Library provides important benefits for students in obtaining quality references, completing their final assignments, and contributing to the development of agricultural, agribusiness, and plantation science and ease of access and completeness of information in the STIP-AP repository collection become the main factor influencing users in searching for information.